Respostas
respondido por:
7
a) x^2 -25/ x^2 +10 +25
(x+5)(x-5) ==> x - 5
(x+5)(x+5) x + 5
b) 5x -10/x^2 -2x
5(x-2) ==> 5
x(x-2) x
c) x+6/ x^3 -36x
x + 6 = (x+6) ==> 1
x(x^2-36) x(x+)(x-6) x(x-6)
(x+5)(x-5) ==> x - 5
(x+5)(x+5) x + 5
b) 5x -10/x^2 -2x
5(x-2) ==> 5
x(x-2) x
c) x+6/ x^3 -36x
x + 6 = (x+6) ==> 1
x(x^2-36) x(x+)(x-6) x(x-6)
respondido por:
9
]a)
b)
c)
Desenvolvendo o denominador, teremos:
Espero ter ajudado ^_^
b)
c)
Desenvolvendo o denominador, teremos:
Espero ter ajudado ^_^
amaral:
obrigado por responderem a minha pergunta. Ajudou muito ^^
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás